Academic Integrity Policy Analysis of Alberta and Manitoba Colleges - Eaton, Sarah Elaine; Vogt, Lisa; Seeland, Josh; Stoesz, Brenda M. (Canadian Perspectives on Academic Integrity, 2023)
Dealing with matters related to academic integrity and academic misconduct can be challenging in higher education. As a result, students, educators, administrators, and other higher education professionals look to policy and procedures to help guide them through these complex situations. Policies are often representative of an institution’s culture of academic integrity. For these and other reasons it is therefore important that policies and procedures are reviewed regularly and updated to ensure that they align with current educational expectations and societal context. In this presentation, we share the results from our policy analysis of 16 colleges in the Canadian western provinces of Alberta and Manitoba. Data extraction and analyses were performed using a tool developed based on Bretag et al.’s five core elements of exemplary academic integrity policy. Our results showed inconsistencies in college polices in terms of the intended audience for the documents (e.g., students, faculty, administrators), varying levels of detail, inconsistent definitions, or categories of misconduct (e.g., plagiarism, cheating) and little mention of contract cheating. We compare the results of this study with previous academic integrity policy research in Canada for colleges in Ontario (Stoesz et al., 2019), as well as universities (Miron et al., 2021; Stoesz & Eaton, 2022). We also discuss the recent increase in the use of artificial intelligence tools such as ChatGPT and GPT-3 and what this could mean in the context of academic integrity policy. We conclude with recommendations for policy reform in the Canadian college context. Our findings may be useful to those working in community colleges and polytechnics elsewhere.